Alveolar size effects on nanoparticle deposition in rhythmically expanding-contracting terminal alveolar models. (June 2020) - Xi, Jinxiang; Talaat, Mohamed; Si, Xiuhua April; Han, Pan; Dong, Haibo; Zheng, Shaokuan
Abstract: Significant differences in alveolar size exist in humans of different ages, gender, health, and among different species. The effects of alveolar sizes, as well as the accompanying breathing frequencies, on regional and local dosimetry of inhaled nanoparticles have not been sufficiently studied. Despite a well-accepted qualitative understanding of the advection-diffusion-sedimentation mechanism in the acinar region, a quantitative picture of the interactions among these factors remains inchoate. The objective of this study is to quantify the effects of alveolar size on the regional and local deposition of inhaled nanoparticles in alveolar models of varying complexities and to understand the dynamic interactions among different deposition mechanisms. Three different models were considered that retained 1, 4, and 45 alveoli, respectively. For each model, the baseline geometry was scaled by ¼, ½, 2, 4, and 8 times by volume. Temporal evolution and spatial distribution of particle deposition were tracked using a discrete-phase Lagrangian model. Lower retentions of inhaled nanoparticles were observed in the larger alveoli under the same respiration frequency, while similar retentions were found among different geometrical scales if breathing frequencies allometrically matched the alveolar size. Dimensional analysis reveals a manifold deposition mechanism with tantamount contributions from advection, diffusion, and gravitational sedimentation, each of which can become dominant depending on the location in the alveoli. Results of this study indicate that empirical correlations obtained from one sub-population cannot be directly applied to others, nor can they be simply scaled as a function of the alveolar size or respiration frequency due to the regime-transiting deposition mechanism that is both localized and dynamic. Graphical abstract: Image 1 Highlights: The effects of alveolar size on nanoparticle deposition were examined in alveolar models with varying complexities. Multiscale velocities exist in the alveoli due to the fluid-wall-particle interactions. Nanoparticle retention in the 45-alveoli model has a much higher sensitivity to geometrical scale than simplified models. Nanoparticle retention rates are similar between alveolar modes with different scales but allometrically matching frequencies. Dimensional analysis provides a quantitative comparison between gravitational, convectional, and diffusional mechanisms.